2021
DOI: 10.1113/jp279771
|View full text |Cite
|
Sign up to set email alerts
|

Role of pattern recognition receptors and the microbiota in neurological disorders

Abstract: In recent years, the gut microbiota has been increasingly implicated in the development of many extraintestinal disorders, including neurodevelopmental and neurodegenerative disorders. Despite this growing connection, our understanding of the precise mechanisms behind these effects is currently lacking. Pattern recognition receptors (PRRs) are important innate immune proteins expressed on the surface and within the cytoplasm of a multitude of cells, both immune and otherwise, including epithelial, endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
(159 reference statements)
0
14
0
Order By: Relevance
“… 373 375 Studies have shown that NOD1/NOD2 may be a new target for the treatment of stress-related gut–brain diseases. 376 The gut–brain axis is a biochemical signal of the digestive tract and central nervous system, which affects all events from brain development to the progression of neurological diseases. The hypothalamic–pituitary–adrenal axis (HPA) is one of the main pathways of gut–brain axis signal transmission.…”
Section: Prr-related Diseasesmentioning
confidence: 99%
“… 373 375 Studies have shown that NOD1/NOD2 may be a new target for the treatment of stress-related gut–brain diseases. 376 The gut–brain axis is a biochemical signal of the digestive tract and central nervous system, which affects all events from brain development to the progression of neurological diseases. The hypothalamic–pituitary–adrenal axis (HPA) is one of the main pathways of gut–brain axis signal transmission.…”
Section: Prr-related Diseasesmentioning
confidence: 99%
“…The major activators of the immune response in neurodegenerative diseases are danger-associated molecular patterns (DAMPs) originating from the damaged tissue, including aggregated proteins and various molecules originating from damaged or dying neurons [61,62]. These endogenous motifs are recognized by pattern recognition recep-tors (PRRs), which include a wide spectrum of receptors such as Toll-like receptors, the nucleotide-binding oligomerization domain leucine rich repeat-containing receptors and scavenger receptors, among others [6,[63][64][65].…”
Section: Neuroinflammation In Neurodegenerative Diseases: the Role Of Nf-κb Pathwaymentioning
confidence: 99%
“…Mice were randomly assigned to wounded or unwounded groups to avoid bias in study design. Sample size calculation was performed using G∗Power (3.1) based on data collected in our previous behavioral experiments showing impairments, where α ​= ​0.05, power [1-β] ​= ​0.8 ( Keogh et al., 2021a , 2021b ). Two days prior to wounding surgery, all mice were sedated with 3–5% isoflourane and the dorsal surface was shaved, depilated wounded, and bandaged.…”
Section: Methodsmentioning
confidence: 99%